A meta‐analysis on the incidence of donor‐related depression after liver transplant. (16th September 2021) - Ng, Cheng Han; Lim, Wen Hui; Lim, Xiong Chang; Xiao, Jieling; Tan, Darren Jun Hao; Syn, Nicholas; Ho, Cyrus S. H.; Kow, Alfred Wei Chieh; Tan, Eunice Xiang Xuan; Fung, James; Muthiah, Mark Dhinesh
Summary: Living donor liver transplantation (LDLT) is increasing, yet gaps exist in the understanding of psychological wellbeing of donors after liver transplant. This meta‐analysis seeks to evaluate the incidence and risk factors for donor‐related depression after liver transplantation. A search was conducted on Medline and Embase database. Articles assessing incidence of depression in LDLT donors were included. Incidence was pooled after Freeman–Turkey double‐arcsine transformation. For risk factors, dichotomous variables were analyzed with generalized linear model, while a conventional meta regression with logit transformation was conducted for continuous variables. Of 1069 abstracts, 40 articles underwent full‐text review. Seventeen articles were included. The pooled incidence of depression among 1888 LT donors was 7.66% (CI: 4.47–12.80%). Depression rates were significantly higher in Asian compared to Western studies (RR: 1.73, CI: 1.19–2.52, P = 0.0039). Female gender ( P < 0.001), Caucasian ethnicity ( P = 0.047), employment status ( P < 0.001) and lower education levels ( P = 0.044) were significantly associated with depression. Donor relationship with recipients was not a significant risk factor. LDLT remains a core aspect of the treatment of end‐stage liver disease. However, the high depression rates after LT suggest that there remains room for improvement in the care of donors' mental health post‐transplant. Abstract : A meta‐analysis on the incidence of donor related depression after liver transplant.